Gene transfer technologies in plants: Roles in improving crops - Khan, K.H. (Recent Research in Science and Technology, 2009)
Gene is a segment of nucleic acid that encodes a functional protein or RNA and is the unit of inheritance. The principle objective of plant biotechnology is to create new varieties of cultivated plants by manipulating DNA molecule. Plant transformation technology has become a versatile platform for cultivar improvement as well as for analysis of gene function in plants. This article discuses and summarizes important work in the literature regarding the gene transfer technologies in plants. The main techniques focused in this article are gene transfer by Agrobacterium tumefaciens, microprojectile bombardment, electroporation of protoplast, polyethylene glycol method, microinjection, silicon carbide mediated transformation, liposome mediated gene transfer and sonication assisted Agrobacterium-mediated transformation. Moreover the application of gene transfer technologies related to the improvement of crops was also focused. This article will help the reader to have an idea on gene transfer technologies and also to the researcher working on plant genetic engineering.